Interest of The Young Generation of Central Kalimantan Towards Educational Games - Misnawati Misnawati; Triyani Triyani; Maryam Mustika; Eli Karliani; Dony Kurniawan; Muh. Safwan (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
This study aims to analyze the interest of the young generation in Central Kalimantan in educational games and how this potential can be maximized to create a positive impact on education. Using a qualitative descriptive method to explore the interest of the young generation in Central Kalimantan in educational games. Data was collected through a survey conducted on the young generation of Central Kalimantan aged 12 to 20 years old, totaling 437 respondents. The survey results show that educational games have a significant appeal among the younger generation of Central Kalimantan, mainly because of the fun challenges and relevant learning content. Although most respondents have tried educational games in the form of quizzes, the intensity of their use is still inferior to action/adventure games that are more popular. Elements such as graphics, engaging stories, and interactive gameplay are also important factors in enhancing the gaming experience. To increase its appeal and effectiveness, developers are advised to integrate entertainment elements such as interactive challenges, in-depth stories, and stunning visual designs to make it more competitive. By combining education and entertainment creatively, educational games have the potential to become an effective learning medium and the main choice of the younger generation.